Comparison of Persistent Symptoms After COVID-19 and Other Non-SARS-CoV-2 Infections in Children - Roge, Ieva; Smane, Liene; Kivite-Urtane, Anda; Pucuka, Zanda; Racko, Iveta; Klavina, Lizete; Pavare, Jana (Frontiers in Pediatrics, 2021)
Introduction:The data on long COVID in children is scarce since children and adolescents are typically less severely affected by acute COVID-19. This study aimed to identify the long-term consequences of SARS-CoV-2 infection in children, and to compare the persistent symptom spectrum between COVID-19 and community-acquired infections of other etiologies. Methods:This was an ambidirectional cohort study conducted at the Children’s Clinical University Hospital in Latvia. The study population of pediatric COVID-19 patients and children with other non-SARS-CoV-2-community-acquired infections were invited to participate between July 1, 2020, and April 30, 2021. Results:In total, 236 pediatric COVID-19 patients were enrolled in the study. Additionally, 142 comparison group patients were also enrolled. Median follow-up time from acute symptom onset was 73.5 days (IQR;43-110 days) in the COVID-19 patient group and 69 days (IQR,58-84 days) in the comparison group. Most pediatric COVID-19 survivors (70%,N=152) reported at least one persistent symptom, but more than half of the patients (53%,N=117) noted two or more long-lasting symptoms. The most commonly reported complaints among COVID-19 patients included persistent fatigue (25.2%), cognitive sequelae, such as irritability (24.3%), and mood changes (23.3%), as well as headaches (16.9%), rhinorrhea (16.1%), coughing (14.4%), and anosmia/dysgeusia (12.3%). In addition, 105 (44.5%) COVID patients had persistent symptoms after the 12-week cut-off point, with irritability (27.6%,N=29), mood changes (26.7% N=28) and fatigue (19.2%,N=20) being the most commonly reported ones. Differences in symptom spectrum among the various age groups were seen. Logistic regression analysis showed that long-term persistent symptoms as fever, fatigue, rhinorrhea, loss of taste and/or smell, headaches, cognitive sequelae, and nocturnal sweating were significantly associated with the COVID-19 experience when compared with the controls. Conclusions:We found that at the time of interview almost three-quarters of children reported at least one persistent symptom, but the majority of patients (53%) had two or more concurrent symptoms. The comparison group’s inclusion in the study allowed us to identify that symptom persistence is more apparent with COVID-19 than any other non-SARS-CoV-2 infection. More research is needed to distinguish the symptoms of long COVID from pandemic-associated complaints. Each persistent symptom is important in terms of child well-being during COVID-19 recovery.